2006
DOI: 10.1111/j.1473-2165.2006.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroquinone and its analogues in dermatology – a risk‐benefit viewpoint

Abstract: Hydroquinone (HQ) has been used since the 1950s in commercially available over-the-counter skin lightener products and since the 1960s as a commercially available medical product. It is also used in cosmetic products such as hair dyes and products for coating finger nails. Beginning in 2001, HQ is no longer authorized for use in cosmetic skin lightening formulations in European Union countries, although products containing arbutin, an analogue of HQ, and botanicals, including plants that naturally contain HQ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 48 publications
0
76
0
Order By: Relevance
“…Those substances may also still be used under strict dermatological supervision. Thus, the presence of hydroquinone, kojic acid, or azelaic acid is totally prohibited in cosmetic formulations by Swiss legislation, whereas hydroquinone is still authorized in the USA, where it is sold as an over-the-counter drug (concentration of hydroquinone not exceeding 2%), and products containing β-arbutin or plants that naturally contain hydroquinone and β-arbutin continue to remain available in European countries [132,150,151]. Moreover, numerous Asian and African countries have yet to legislate about the safety status of such substances [23].…”
Section: Current Regulationsmentioning
confidence: 99%
“…Those substances may also still be used under strict dermatological supervision. Thus, the presence of hydroquinone, kojic acid, or azelaic acid is totally prohibited in cosmetic formulations by Swiss legislation, whereas hydroquinone is still authorized in the USA, where it is sold as an over-the-counter drug (concentration of hydroquinone not exceeding 2%), and products containing β-arbutin or plants that naturally contain hydroquinone and β-arbutin continue to remain available in European countries [132,150,151]. Moreover, numerous Asian and African countries have yet to legislate about the safety status of such substances [23].…”
Section: Current Regulationsmentioning
confidence: 99%
“…However, the recent discovery of their adverse side effects suggests that the applicability of these chemicals might be limited. It has been reported that kojic acid can cause allergic contact dermatitis [21] and that arbutin might carry carcinogenic risks [22] . Moreover, low stabili-www.nature.com/aps Yao C et al Acta Pharmacologica Sinica npg ties or high costs of available agents may also be issues of concern.…”
Section: Introductionmentioning
confidence: 99%
“…Here follows the Felix von Luschan's chromatic scale [8,9] (Fig. 1) and in the successive Table I refer, it is possible to notice how the values decreases day after day.…”
Section: Methodsmentioning
confidence: 99%
“…The bleaching agents are not but herbs that contain high percentages of arbutin [7,8], that when in contact with the sweat of the skin, drives to hydroquinone.…”
Section: For Instancementioning
confidence: 99%